Triple hop test ability performed by athletes in the regional athletic center during the competition period - Sudarko, Rumpis Agus; Sukamti, Endang Rini; Alim, Abdul; Nurfadhilah, Risti; Pamungkas, Okky Indera; Miftachurochmah, Yulvia (Universitas Negeri Yogyakarta, 2023)
Tests and Measurements, is an integral part of various human activities, as well as in sports training activities. This research is a quantitative descriptive study. The population that the researchers determined was in regional training center athletes in the Special Region of Yogyakarta. Sampling techniques are carried out by purposive random sampling, namely athletes who enter the regional training center in the Special Region of Yogyakarta, so that a number of 106 athletes are obtained. The instrument used to collect the research data used the triple hop test to determine the athlete's ability level. The data in quantitative research obtained from respondents is tabulated then calculated the percentage, and then analyzed. The instrument used to collect the research data used the triple hop test to determine the athlete's ability level. The data in quantitative research obtained from respondents is tabulated then calculated the percentage, and then analyzed. The results, it can be argued that the average level of the level of triple hop ability of regional training center athletes during the periodization of competition is in the less category for each category of men and women. Therefore, it is necessary to provide special evaluation and treatment.